Insights into the substrate specificity of the MutT pyrophosphohydrolase using structural analogues of 8-oxo-2′-deoxyguanosine nucleotide - Hamm, Michelle L. (Bioorg Med Chem Lett, 2016)
The bacterial repair enzyme MutT hydrolyzes the damaged nucleotide OdGTP (the 5′-triphosphate derivative of 8-oxo-2′-deoxyguanosine; OdG), which is a known mutagen and has been linked to antibacterial action. Previous work has indicated important roles for the C8-oxygen, N7-hydrogen, and C2-exocyclic amine during OdGTP recognition by MutT. In order to gain a more nuanced understanding of the contribution of these three sites to the overall activity of MutT, we determined the reaction parameters for dGTP, OdGTP, and nine of their analogues using steady state kinetics. Our results indicate that overall high reaction efficiencies can be achieved despite altering any one of these sites. However, altering two or more sites leads to a significant decrease in efficiency. The data also suggest that, similar to another bacterial OdG repair enzyme, MutM, a specific carbonyl in the enzyme can not only promote activity by forming an active site hydrogen bond with the N7-hydrogen of OdGTP, but can also hinder activity through electrostatic repulsion with the N7-lone pair of dGTP.